Obtención de un extracto vegetal de la ortiga mayor (urtica dioica) por maceración con calor para la elaboración de queso fresco - Yasig Quinga, Olga Marbel (2019)
This research was carried out at faculty of Agricultural Sciences and Natural Resources of Universidad Técnica de Cotopaxi. The greater nettle (Urtica dioica) is a plant commonly used to treat diseases because of their urticate properties. People do not use this plant on the food industry, thus the research objective was to take advantage of nettle leaves and get an extract to use on agro industrial field. The investigation consisted on getting the extract from the greater nettle leaves through maceration with heat physical-chemical analysis (pH, acidy) and protein quantification in an accredited laboratory (INIAP) of all the treatments. The researchers put through the nettle leaves to different stages of maceration (40min, 30min, and 20min) with different proportions of water, depending the amount of leaves used (1:1, 2:1, 3:1). The process result, the researchers obtained nine treatments with their respective repetition; the researchers performed each extract a physical-chemical and bromatology (proteins). According to the statistical evaluation made by ANOVA analysis in INFOSTA T/L. It showed meaningful differences in the protein content, pH and acidy, allowing to determine the best treatments, the extract with the best protein content was the t4 (maceration for 30 minutes with a proportion 1:1 (100 ml of water – 100g of nettles leaves) getting as a result 0, 68% of protein content. Regarding to the pH and acidy the best treatment was (100g of nettles leaves, with 300 ml of water with 30 min of maceration). The best pH was 5, 76, with an acidity of 0, 15 being the closest value to the commercial rennet that are included between (5, 2- 5, 8).